Analysis of the physical condition profile of athletes in Tangerang City's Measurable Sports Branch as Part of the Porprov Banten 2022 Preparation: Descriptive study - Iwan Hermawan; Fahmy Fachrezzy; Uzizatun Maslikah; Puspo Nagati Paramita Namira Khanza; Gatot Jariono (UNIB Press, 2022)
The study was conducted from August to October 2022. The data collection was taken at the Tangerang City Fort Stadium. The research sample is Tangerang City Athletes who will be prepared in Porprov Banten 2022. The instruments of this study are (1) an Anthropometric Test consisting of height (cm) and Weight (kg), (2) a Biomotor Ability Test or Physical ability consisting of a Flexibility Test with cm units, an Explosive power test of limb muscles using Vertical Jump with centimeters (cm) assessment unit, Abdominal muscle strength test with Push-ups with the unit of assessment of the number of performed in 1 minute. Data analysis techniques in this study use Descriptive Analysis. The method used in this study is Descriptive Quantitative and is an approach to finding the answer to the problem through the formulation of the problem that has been formulated, namely the Profile of the Physical Condition of Tangerang City Athletes in the Context of Preparing for Porprov Banten 2022 which is seen from the physical profile that is tested and measured is Anthropometry, and Biomotor components.